The Correlation Between Body Mass Index Genetic Risk Score and Dietary Intake on Weight Status: A Systematic Review - Budi, Agus; Farida, Farida (International Medical Journal Corp. Ltd, 2024)
Background: Obesity is associated with environmental factors, such as dietary intake and physical activity, as well as genetic factors. Obesity is due to an increase in total energy intake, although the precise contributions of nutrients (for example, carbohydrates, fat, protein and fiber) are not fully understood. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using Medline, Science Direct, Scopus and Embase, among other online venues. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: More controlled clinical trials with robust designs are needed to be able to recommend personalized nutrition based on nutrition for obesity prevention and management.